Modular modelling and simulation tool for evaluation of powertrain performance. (29th October 2004) - Eriksson, A.; Jacobson, B.
A modelling and simulation tool for evaluation and comparison of powertrain concepts is described. It is built upon an existing modelling and simulation software package. The tool uses new and powerful modelling techniques for dynamic systems. Object and equation orientation and hierarchically structured libraries are used to provide a powerful yet flexible instrument. The powertrain is studied as part of a total system consisting of vehicle, driver and road. Transient city traffic is focused on. Primary results from simulations are energy consumption and emissions. Simple modelling examples demonstrate the advantages of equation-oriented modelling. New kinds of road and driver models are also included. They make prediction of the outcome of realistically described transportation tasks possible and are useful for evaluating the influence of driver behaviour on energy consumption and emissions. Examples of model implementation and library structure are presented. The ability of the tool is illustrated with simulations which are compared with tests.